Conflitos no Chifre da África: oportunidades e constrangimentos da difusão do poder - Carvalho, Daniel Duarte Flora (2010)
This study considers the opportunities and constraints of broadcasting power in Africa to investigate the causes of the wars in the Horn of Africa. The power broadcast over population pattern, the multiples centres of power and the actions of the many state and non-state actors are determinants to the outbreak or not of conflicts in Africa. Once this pattern is identified in the Horn of Africa which, by its long tradition of statehood and its great Westphalian sense, is mistakenly seen as an exception to the African model, we look forward to verify what the war reasons in this region are. This study so makes an approach on the war between Ethiopia and Eritrea and the very constitution of the Ethiopian state and concludes that not only the Horn of Africa is inserted in the pattern of broadcasting power on populations which is common to the Sub Saharan Africa and that such a pattern is the causes of war in that region